Influence of biofertilizes and NAA on growth and yield of Chilli (Capsicum annuum L.) CV. JM-283 - Athaneria, Moresh Kumar; Sengar, Nisha; Pandey, BR (Vegetable Science, 2011)
India is the largest producer of chillies in the World. The indiscriminate use of inorganic fertilizer leads to nutrient imbalance in soil causing ill effect on soil health. Therefore, there is need to supplement the inorganic fertilizers along with organic and biofertilizer to maximum possible level. Biofertilizers are an important component of organic farming they are less expensive, eco-friendly and sustainable, do not require non-renewable source of energy during their production and improve crop growth and quality of crops. They increase sustainability of the soil and make it more productive. The production of chilli is reduced due to flower and fruit drop, which is caused by physiological and hormonal imbalance in the plants particularly under unfavorable environments, such as extremes of temperature i.e. too low or high temperature (Erickson and Makhart, 2001). Studies on the effect of plant growth regulators in solanaceous fruit and vegetable crops have revealed that the application of some of the plant growth regulators has been found